Exploring Human Milk, Nutrition, Growth, and Breastfeeding Rates at Discharge(HUMMINGBIRD Study): a protocol for a pilot randomised controlled trial - Judith Rankin; Natalie Shenker; Janet Berrington; Stefan Zalewski; Nick Embleton; Kristina Chmelova (BMJ Publishing Group, 2023)
Introduction Mother's own breast milk (MOM) is the optimal nutrition for preterm infants as it reduces the incidence of key neonatal morbidities and improves long-term outcomes. However, MOM shortfall is common and either preterm formula or pasteurised donor human milk (DHM) may be used, although practice varies widely. Limited data suggest that the use of DHM may impact maternal beliefs and behaviours and therefore breastfeeding rates. The aim of this pilot study is to determine if longer duration of DHM exposure increases breastfeeding rates, and if a randomised controlled trial (RCT) design is feasible.Methods and analysis The Human Milk, Nutrition, Growth, and Breastfeeding Rates at Discharge (HUMMINGBIRD) Study is a feasibility and pilot, non-blinded RCT with a contemporaneous qualitative evaluation. Babies born less than 33 weeks' gestation or with birth weight <1500 g whose mothers intend to provide MOM are randomly assigned to either control (DHM used to make up shortfall until full feeds and preterm formula thereafter) or intervention (DHM used for shortfall until 36 weeks' corrected age or discharge if sooner). The primary outcome is breast feeding at discharge. Secondary outcomes include growth, neonatal morbidities, length of stay, breastfeeding self-efficacy and postnatal depression using validated questionnaires. Qualitative interviews using a topic guide will explore perceptions around use of DHM and analysed using thematic analysis.Ethics approval and dissemination Nottingham 2 Research Ethics Committee granted approval (IRAS Project ID 281071) and recruitment commenced on 7 June 2021. Results will be disseminated in peer-reviewed journals.Trial registration number ISRCTN57339063.